Patterns of c-reactive protein RATIO response in severe community-acquired pneumonia: a cohort study - Coelho, Luís M. (2012)
Centro Hospitalar de Lisboa Ocidental. Hospital de São Francisco Xavier. Polyvalent Intensive Care. Lisboa, Portugal / Hospital de São Francisco Xavier. Faculty of Medical Sciences. CEDOC, Lisboa, Portugal.